Identification et aptitudes technologiques des bactéries lactiques du J’ben de chèvre - ZBALAH, ROUISSAGE (My University, 2017)
The study carried out, allowed us to identify lactic acid bacteria from Algerian goat’s Jben from Naâma. And to test their technological skills, in a community, such as acidity, and proteolytic activity. The proteomic identification of the 38 isolates by the MALDI-TOF MS technique revealed a dominance of the genus Enterococcus was observed about 66%, and a total absence of the genus Lactobacillus in the samples studied. After identification, we selected a community of five different strains for assessment of technological suitability (including two Leuconostoc mesenteroides, two Lactococcus lactis, and one Enterococcus durans). The results obtained indicate that the community has good acidifying power, and no proteolytic activity.
Keywords: Isolates.; goat’s cheese; identification; community; technological skills; MALDI-TOF MS; Isolats.; J’ben de chèvre; identification; communauté; aptitudes technologiques